Numerical solution of nonlinear dual‐phase‐lag model for analyzing heat transfer in tissue during thermal therapy. Issue 6 (5th August 2021) - Sharma, Neha; Singh, Surjan; Kumar, Dinesh
Abstract: This article deals with mathematical modeling and simulation of heat transfer in tissue under periodic boundary condition using nonlinear dual‐phase‐lag‐bioheat‐transfer (DPLBHT). We have taken the temperature dependent blood perfusion and metabolic heat source as exponent variation in nonlinear DPLBHT model, both are experimentally validated function of temperature. In this article we applied finite difference method and Runge–Kutta (4, 5) scheme to solve nonlinear problem. In particular case the exact solution is obtained and compared with numerical scheme and both are in good agreement. Effect of different parameters are discussed in detail such as blood perfusion rate, dimensionless heat source parameters, relaxation, and thermalization time on dimensionless temperature. The whole article is analyzed in dimensionless form.